An effective concentration of propolis extract to inhibit the activity of Streptococcus mutans glucosyltransferase enzyme - Riyan Iman Marsetyo; Sagita Putri Andyningtyas; Chonny Salsabilla Zamrutizahra; Ivan Nur Fadela; Agus Subiwahjudi; Ira Widjiastuti (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: According to Riset Kesehatan Dasar (Riskesdas) (2013) and the World Health Organisation (WHO), caries is still a global problem and highly prevalent in Indonesia. Caries is mainly caused by Streptococcus mutans with virulence factors known as glucosyltransferase (GTF). The GTF enzyme contribute to the pathogenesis of caries by converting sucrose to fructose and glucan, which are then used in the formation of biofilms and dental plaques. Natural propolis compounds containing flavonoids, terpenoids, saponins and tannins, can inhibit GTF enzyme activity. Purpose: This study aimed to determine an effective concentration of propolis extract for inhibiting the S. mutans GTF enzyme activity. Methods: This study used propolis extract at 14 μg/ mL, 16 μg/m and 1 μg/mL to determine the inhibitory effect on S. mutans GTF enzyme activity. The GTF enzyme were obtained from the supernatant from S. mutans culture centrifugation. The GTF enzyme activity was measured using high-performance liquid chromatography (HPLC) to calculate the fructose level. Results: The mean fructose concentration at 14 μg/mL, 16 μg/mL, and 18μg/mL were 3.31%, 1.56%, and 0.29%, respectively. Conclusion: The most effective concentration of propolis extract for inhibiting the effect of S. mutans GTF enzyme activity is 14 μg/mL.